Challenges and opportunities nurses experienced to turn conference presentations into journal articles - Lizeth Roets; Yvonne Botma (Elsevier, 2018)
Background: Nurses need to build their professional knowledge base through the publication of research findings in scientific journals. Substantial preparation goes into the preparation of a conference presentation, which could form the basis of a subsequent publication. Methods: A descriptive single case study design with multiple data types was used to describe the extent to which nurses from Southern Africa convert their conference presentation into journal articles; and to describe the prohibiting or supporting issues they experience in converting their conference presentations into journal articles. Setting and participants: Nurses in low and middle-income countries form the backbone of health services in for example the Southern African region. Many of those nurses present papers at annual regional nursing conferences. Data collection: Administrative staff from three reputable nursing organisations sent recruitment and information letters to the members on the databases, requesting them to complete a short questionnaire via SurveyMonkey™. The questionnaire comprised closed and open-ended questions. The software of SurveyMonkey™ automatically performed descriptive analyses of the closed-ended questions. The researchers analysed the narrative data obtained via the open-ended questions through open inductive coding. Results: The majority of nurses (78,3%) who attended and/or presented papers at an international conference had at least a master's degree and are therefore no strangers to research. However, only 46 individuals reported 70 publications that derived from conference presentations over the last 5 years. Positive feedback from reviewers and receiving incentives were identified, among others, as motivators while common inhibitors were the complexity related to the writing, submitting and reviewing processes as well as the lack of dedicated time. Conclusions: Contextual factors such as offering parallel programmes, supplementing an insufficient income with consultation work, lack of time and incentives, and lack of mentors to guide novices through the complex process of writing and submitting articles may be more pronounced in low and middle-income countries than in developed countries. A comparison between the north-south rate of converting conference presentations into journal articles may provide further light on this topic. Keywords: Conference presentations, Dissemination of research results, Nurse researchers, Publications